2012
DOI: 10.5114/aoms.2012.29220
|View full text |Cite
|
Sign up to set email alerts
|

Dual-source computed tomography angiography and intravascular ultrasound assessment of restenosis in patients after coronary stenting for bifurcation left main stenosis: a pilot study

Abstract: IntroductionThe aim of this prospective study was to evaluate the diagnostic accuracy of dual-source computed tomography coronary angiography (CTCA) compared to intravascular ultrasound (IVUS) for the detection of restenosis in patients who underwent coronary stenting for bifurcation left main (LM) stenosis.Material and methodsTwenty-four patients underwent percutaneous intervention of the LM and were subsequently examined (median 9.2 months after procedure) using IVUS and CTCA for the detection of restenosis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Drug-eluting stents (DES) have become the most widely used coronary stents in clinical practice [ 1 ]. A number of clinical trials have verified the benefits of DES in reducing the rates of in-stent restenosis or target lesion revascularization (TLR) compared with bare metal stents in unselected patients with coronary artery diseases [ 2 4 ]. Patients with diabetes are especially prone to restenosis after stenting, making DES preferable to bare-metal stents in this patient population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Drug-eluting stents (DES) have become the most widely used coronary stents in clinical practice [ 1 ]. A number of clinical trials have verified the benefits of DES in reducing the rates of in-stent restenosis or target lesion revascularization (TLR) compared with bare metal stents in unselected patients with coronary artery diseases [ 2 4 ]. Patients with diabetes are especially prone to restenosis after stenting, making DES preferable to bare-metal stents in this patient population [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many novel techniques, including quantitative coronary angiography (QCA), coronary CT angiography (CCTA), cardiac magnetic resonance myocardial perfusion imaging (CMR-MPI), intravenous ultrasound (IVUS), optical coherence tomography (OCT), dynamic 3-dimensional CMR, have emerged with FFR as a functional gold standard for the assessment of hemodynamically significant lesions [ 33 41 ] ( Table II ). The results suggested that minimal lumen diameter (MLD) and lesion length (LL) measured by QCA were well correlated with FFR values, which indicated that both MLD and LL had physiological significance in coronary lesions [ 33 35 , 38 , 39 ]. Transluminal attenuation gradient (TAG) and corrected coronary opacification (CCO), as two of the novel analyses of CCTA, have not been physiologically validated [ 36 ].…”
Section: Fractional Flow Reserve As Functional Gold Standardmentioning
confidence: 99%
“…The level of calcification of vessels and aortic valve can be determined using computed tomography (CT). The examination also allows the lumen and wall of a vessel to be evaluated, and provides information regarding the morphology of the aortic valve – the number of cusps, presence of raphe and area of the valve [ 16 21 ].…”
Section: Introductionmentioning
confidence: 99%